(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Despite great advances in hemodialysis, complications during dialysis remain in force. Accurate assessment of dry weight is a determining factor in the prevention of hemodialysis complications. This study is designed to evaluate the effect of adjustment of ultrafiltration rate, on hemodialysis complications, based on dry weight calculation, by measuring the pre-dialysis serum sodium. Methods. In this single-blind clinical trial 50 patients were included. The patients were randomly divided into case and control groups. First, in the intervention group, the blood sodium level was measured before dialysis. Then, the dry weight of the patients was determined, ultrafiltration was adjusted according to the dry weight, and the patients’ dialysis program was performed. In the control group, dry weight was determined routinely. Blood pressure, muscle cramps, nausea, and vomiting were recorded in both groups for 3 months. Results. The results showed a significant difference between the two groups in the rate of postoperative nausea and vomiting (P < .05) and muscle cramps during dialysis (P < .05). There were no significant differences between the two groups in blood pressure drop during dialysis and fatigue after hemodialysis in the first, second, and third months (P > .05). Conclusion. Accurate assessment of dry weight by the pre-dialysis blood sodium formula, reduces muscle cramps, nausea, and, vomiting. DOI: 10.52547/ijkd.7170